'Anwar serves Zionist interests' - Mohd, Hariz (New Straits Times, 2012)
KUALA LUMPUR : Opposition leader Datuk Seri Anwar Ibrahim's support for Israel's security efforts is a signal to the Zionist regime and the United States that he is their man.